Class control of the practical lesson for students of physical education and sports sciences from the point of view of university professors the two researchers (Journal of the College of Basic Education, 2022)
The research aims to identify the classroom control of the practical lesson for students of the Department of Physical Education, Sports Science and Sports Science in the College of Basic Education at Al-Mustansiriya University The researcher used the descriptive approach in the survey method because it is more appropriate to the nature of his research.The research community consists of the teachers of the Department of Physical Education and Sports Sciences in the College of Basic Education in the province of Baghdad. The surveys were chosen at random. The researcher used the classroom control scale for the practical lesson in the colleges and departments of physical education and sports sciences in Baghdad, which was previously built by the researcher and which is compatible with the nature of the research community. The scale consists of three axes: the guiding style, the reprimanding style, and theAnd the punitive method, and for the purpose of knowing the clarity of the instructions and paragraphs, the scale of classroom control patterns and calculating the answer time, the researcher resorted to doing an exploratory experiment that was applied to a random sample of (8) two teachers from outside the research sample, and the researcher extracted the psychometric properties of the scale The statistical package (spss) was used to extract the statistical means, and after presenting, analyzing and discussing the results, the researcher reached the following results:1- The indicative method occupied the first rank within the descending order in choosing the methods of class control, with an arithmetic mean of (37.01) with significant differences.2-The reprimanding method occupied the second rank within the descending order in choosing the methods of class control, with an arithmetic mean of (24.77) with significant differences.3-The punitive method occupied the third rank within the descending order in the choice of classroom control methods, with an arithmetic mean of (14.89) with random differences.